2008
DOI: 10.1007/s11695-008-9445-7
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Adjustable Gastric Banding for Morbid Obesity in a Patient with Situs Inversus Totalis

Abstract: Laparoscopic surgery with situs inversus may pose particular challenges to the surgeon. We discuss a case of undiagnosed situs inversus totalis in a morbidly obese patient undergoing laparoscopic adjustable gastric banding (LAGB). The patient was a 29-year-old male with a body mass index (BMI) of 56. There was no prior knowledge of his situs inversus totalis, which was only discovered during laparoscopy at the time of surgery. The operative challenges are discussed. LAGB was performed successfully without comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 5 publications
0
29
0
Order By: Relevance
“…Laparoscopy has been reported for gastric banding,[12] lap assisted gastropexy in a child. [13] Hemicolectomy, distal gastrectomy, fundoplication has also been done laparoscopically.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopy has been reported for gastric banding,[12] lap assisted gastropexy in a child. [13] Hemicolectomy, distal gastrectomy, fundoplication has also been done laparoscopically.…”
Section: Discussionmentioning
confidence: 99%
“…Matar [7] described the modifications in the surgical technique and preoperative assessment and the preparedness on the part of the surgeon. A case of undiagnosed SIT in a morbidly obese patient who underwent LAGB was reported by Samaan et al Although there was subsequent gastric band erosion in this case, he concluded that this complication was due to the greater dissection and mobilization of the more posterior placed and less mobile fundus, not due to his situs inversus, and he still considered that gastric banding is a safe method in SIT [2].…”
Section: Discussionmentioning
confidence: 76%
“…The National Institutes of Health has concluded that surgical therapy offers the best long-term chance of successfully treating morbid obesity for most patients [1]. Laparoscopic adjustable gastric banding (LAGB) procedure accounts for nearly 25% of bariatric procedures worldwide [2]. Besides this, in super-obese patients, intragastric balloon application provides satisfactory weight loss in preparation for bariatric surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Laparoscopic surgery has been performed for SIT patients in numerous case reports, including laparoscopic cholecystectomy [12], laparoscopic colectomy [13], laparoscopic fundoplication [14], and laparoscopic gastric band surgery [15]. In 2003, LADG for gastric cancer in a patient with SIT was successfully performed in Japan, and was the first reported case of its kind [2].…”
Section: Discussionmentioning
confidence: 99%